2019 9th International Conference on Information Science and Technology (ICIST) 2019
DOI: 10.1109/icist.2019.8836897
|View full text |Cite
|
Sign up to set email alerts
|

Force Estimation Based on sEMG using Wavelet Analysis and Neural Network

Abstract: In order to meet the needs of sEMG signal control in human-computer interaction, an estimation of grip force based on wavelet analysis and neural network is proposed. Firstly, the acquisition of EMG signals and the extraction methods of traditional features are described based on the introduction platform. Then, the wavelet decomposition and reconstruction algorithm is used to analyze the sEMG signals and extract the corresponding energy characteristics. Different grasp force of and sEMG signals are collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although prior studies that employed ANNs achieved relatively high prediction accuracy, there are some limitations with their approach. Some models only predicted force accurately at specific hand postures (Choi et al, 2010; Ma et al, 2020), whereas another only analyzed accuracy among the training dataset (Jiang et al, 2019). In addition, no prior studies that the authors are aware of have explored the accuracy of hand posture or force prediction while varying repetition rate and duty cycle in a novel dataset, both of which are important characteristics of tasks performed in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prior studies that employed ANNs achieved relatively high prediction accuracy, there are some limitations with their approach. Some models only predicted force accurately at specific hand postures (Choi et al, 2010; Ma et al, 2020), whereas another only analyzed accuracy among the training dataset (Jiang et al, 2019). In addition, no prior studies that the authors are aware of have explored the accuracy of hand posture or force prediction while varying repetition rate and duty cycle in a novel dataset, both of which are important characteristics of tasks performed in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent studies that have successfully shown the value of using ANNs to predict grip force in controlled settings (Choi et al, 2010; Jiang et al, 2019; Ma et al, 2020), ANNs have not yet been used to predict hand posture or force during tasks with varying repetition rate or duty cycle (time spent in exertion). Additionally, prior studies have applied ANN prediction models to similar datasets by splitting the data into training and test datasets and reporting prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the literature review, extracting discriminative features from 1-D ECG signals ignores their frequency domain characteristics and lacks discriminatory features [6][7], [23]. Moreover, performing the classification via 2D images format has reached higher than using the 1D time-domain signal.…”
Section: -D Mapping Generation Using Time-frequency Techniquesmentioning
confidence: 99%
“…Some of the literature methods classified different types of muscle movements based on sEMG signals. Jiang et al [23] presented an sEMG signals analysis method using discrete Wavelet Transform (DWT) for detecting and characterizing signal patterns. They adopted traditional feature extraction techniques using an external feature extraction process.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that machine learning is a more robust approach to predicting force or classification problems (Subasi et al, 2006;Choi et al, 2010). Recent studies have successfully reported the accuracy of using artificial neural networks (ANN) to predict grip force in controlled settings (Choi et al 2010;Jiang et al, 2019;Ma et al, 2020;Wang et al, 2020). Accuracy computed based on confusion matrices has been the most popular adopted metrics in binary classification tasks.…”
Section: Introductionmentioning
confidence: 99%